Severe Flooding in the Atoll Nations of Tuvalu and Kiribati Triggered by a Distant Tropical Cyclone Pam - Hoeke, Ron K.; Damlamian, Herve; Aucan, Jérome; Wandres, Moritz (Frontiers in Marine Science, 2021)
Tropical cyclone (TC) Pam formed in the central south Pacific in early March 2015. It reached a category 5 severity and made landfall or otherwise directly impacted several islands in Vanuatu, causing widespread damage and loss of life. It then moved along a southerly track between Fiji and New Caledonia, generating wind-waves of up to approximately 15 m, before exiting the region around March 15th. The resulting swell propagated throughout the central Pacific, causing flooding and damage to communities in Tuvalu, Kiribati and Wallis and Futuna, all over 1,000 km from TC Pam’s track. The severity of these remote impacts was not anticipated and poorly forecasted. In this study, we use a total water level (TWL) approach to estimate the climatological conditions and factors contributing to recorded impacts at islands in Tuvalu and Kiribati. At many of the islands, the estimated TWL associated with Pam was the largest within the ∼40-year period of available data, although not necessarily the largest in terms of estimated wave setup and runup; elevated regional sea-level also contributed to the TWL. The westerly wave direction likely contributed to the severity, as did the locally exceptional storm-swell event’s long duration; the overall timing and duration of the event was modulated by astronomical tides. The findings of this study give impetus to the development, implementation and/or improvement of early warning systems capable of predicting such reef-island flooding. They also have direct implications for more accurate regional flood hazard analyses in the context of a changing climate, which is crucial for informing adaptation policies for the atolls of the central Pacific.